Bank lending channel for monetary policy transmission in Malaysia: An ARDL approach - Goh, K.L.; Chong, C.S.; Yong, S.L. (Euro-American Association of Economic Development Studies, 2007)
The relevance of bank lending channel for the transmission process of monetary policy in Malaysia is investigated using the autoregressive-distributed lag (ARDL) model. The newly developed bounds test (Pesaran, et al. 2001) is employed to determine the specification of this model. Deposits tend to fall following contractionary monetary policy shocks, but banks are able to cushion their loan customers from the reduction in deposits through adjustments in liquid financial instruments. As such, these monetary shocks did not depress growth in loans. Although a shift is witnessed in the country’s interest rate regime as a policy response to the recent East Asian currency crisis, evidence was not found to support the effectiveness of the bank lending channel for the transmission of monetary policy.